Analysis of the general match profile of international rugby union between 2007 and 2013 - Kraak, W.; Coetzee, F.; Venter, R. (International Journal of Performance Analysis in Sport, 2017)
Law amendments are fundamental to the development of rugby and are introduced for a variety of reasons. The aim of this study was to investigate and compare the general match profile of international rugby between 2007 and 2013 in order to determine the effect of law changes. The researchers made use of mixed method methodology approach for this study. For the quantitative approach, a total of 248 matches were recorded and analyzed using the Fairplay video analysis software package. For the qualitative approach, the researchers conducted semi-structured interviews with expert coaches, specialist coaches, players and referees and referee coaches. The results revealed a practical significant decrease in the number of scrums (d = 1.03) line-outs (d = .86), rucks (d = .86), mauls (d = .62) and kicks (d = .46). An increase in the number of passes (d = .43), ball carries (d = 1.22) tackles attempted (d = .65) and penalty kicks (d = .98) between 2007 and 2013 was observed. The interviews revealed that under the current laws, there is an imbalance between attack and defence. The general match profile of international rugby has moved to a game with a decrease in the number of set pieces and kicks to an increase in the number of ball carries and tackles.